Analysis Of The Level Of Understanding Of MSME Actors Towards SAK-EMKM Along The University Of North Sumatra Road From Door 1 To Door 4 - Sari, Adila; Pricillia Deborah Valentine; Nayla Nurul Putri; Nuraini Azlin; Heriyati Chrisna (Indonesian Journal Publisher, 2025)
This study aims to determine the degree of interpretation of Micro, Small, and Medium Enterprises (MSMEs) compared to the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and analyze its application. This information was obtained from a survey of 168 MSME respondents on Jalan Universität North Sumatra (doors 1–4). The findings of the study show that most MSMEs do not understand the SAK EMKM, with 90% of respondents not knowing the standards and 84 respondents answering